Pharmacological therapy of spondyloarthritis. (July 2015) - Palazzi, Carlo; D'Angelo, Salvatore; Gilio, Michele; Leccese, Pietro; Padula, Angela; Olivieri, Ignazio
<x xml:space="preserve">Abstract</x> Introduction: The current pharmacological therapy of spondyloarthritis (SpA) includes several drugs: Non-steroidal anti-inflammatory drugs, corticosteroids, traditional disease-modifying antirheumatic drugs and biologic drugs. Areas covered: A systematic literature search was completed using the largest electronic databases (Medline, Embase and Cochrane), starting from 1995, with the aim to review data on traditional and biologic agents commercialised for SpA treatment. Randomised controlled trials and large observational studies were considered. In addition, studies performed in SpA patients treated with other, still unapproved, drugs (rituximab, anti-IL6 agents, apremilast, IL17 inhibitors and anakinra) were also taken into account. Expert opinion: Biologic agents, especially anti-TNF drugs, have resulted in significant progress in improving clinical symptoms and signs, reducing inflammatory features in laboratory tests and imaging findings, and recovering all functional indexes. Anti-TNF drugs have radically changed the evolution of radiographic progression in peripheral joints; the first disappointing data concerning their efficacy on new bone formation of axial SpA has been recently challenged by studies enrolling patients who have been earlier diagnosed and treated. The opportunity to extend the interval of administration or to reduce the doses of anti-TNF agents can favourably influence the costs. Ustekinumab, the first non-anti-TNF biologic drug commercialised for psoriatic arthritis, offers new chances to patients that are unresponsive to anti-TNF.